Author Correction: Both higher fitness level and higher current physical activity level may be required for intramyocellular lipid accumulation in non-athlete men - Nozomu Yamasaki (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.